Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd010036
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of posterior decompression techniques compared to conventional laminectomy for lumbar stenosis

Abstract: Purpose To compare the effectiveness of techniques of posterior decompression that limit the extent of bony decompression or to avoid removal of posterior midline structures of the lumbar spine versus conventional facetpreserving laminectomy for the treatment of patients with degenerative lumbar stenosis. Methods A comprehensive electronic search of the Cochrane Central Register of Controlled Trials, MED-LINE, EMBASE, Web of Science, and the clinical trials registries ClinicalTrials.gov and World Health Organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 35 publications
0
42
0
1
Order By: Relevance
“…However, partial removal of the facet joint may lead to joint instability and subsequent spondylolisthesis and scoliosis (35). Biomechanical studies have demonstrated that facet joints constrain axial rotation and flexion (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…However, partial removal of the facet joint may lead to joint instability and subsequent spondylolisthesis and scoliosis (35). Biomechanical studies have demonstrated that facet joints constrain axial rotation and flexion (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…We employed the methods of Overdevest et al 60 in setting the MCID to a 30% improvement from the mean of the baseline level of pain. This corresponded to 1.5 points on a VAS and 2.0 points on an NRS for the data examined here.…”
Section: Methodsmentioning
confidence: 99%
“…Minimally invasive surgery has conflicting evidences 72) . The evidence supporting superiority of posterior decompression techniques is of low quality 73) . The large cohort study suggests that addition of fusion to decompression is not associated with an improved outcome 74) .…”
Section: Surgerymentioning
confidence: 99%